2021
DOI: 10.3390/ijerph182111223
|View full text |Cite
|
Sign up to set email alerts
|

Social Distancing in Tourism Destination Management during the COVID-19 Pandemic in China: A Moderated Mediation Model

Abstract: While protective measures in response to infectious diseases may reduce the freedom of tourists (regarding their behaviors), few studies have documented the effects of destination protective measures on the self-protective behaviors of tourists. By applying the protection motivation theory, this study examines the effects of perceived destination protective supports on the social distancing intentions of tourists during the COVID-19 pandemic. The results reveal significant relationships among perceived destina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Threat appraisal is moderated by social norms, but they may outweigh perceived hazards and motivate consumers to use computer services (Chi et al, 2012 ). Zhang et al ( 2021 ) study confirmed that social norm moderates the association between threat appraisal and social distancing intention. Accordingly, we propose the following hypotheses: H7a: There is a moderating role of social norms in the link between shoppers’ risk and their desire to stay a shorter time at the shopping mall.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 81%
See 1 more Smart Citation
“…Threat appraisal is moderated by social norms, but they may outweigh perceived hazards and motivate consumers to use computer services (Chi et al, 2012 ). Zhang et al ( 2021 ) study confirmed that social norm moderates the association between threat appraisal and social distancing intention. Accordingly, we propose the following hypotheses: H7a: There is a moderating role of social norms in the link between shoppers’ risk and their desire to stay a shorter time at the shopping mall.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 81%
“…A prior study conducted by Liu et al ( 2021 ) provided confirmation that protective motivation has a large and favourable influence on behavioural intention. According to Zhang et al ( 2021 ), consumer protection motivation and behavioural intention are positively correlated in the setting of omnichannel marketing. As a result, the following theory was put out by this investigation: H6 : Shopper’s protection motivation significantly affects the desire to stay a shorter time at the shopping mall.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Results of the survey indicate a significant impact of Covid19 on developıng digital service capability. Thus, Covid19 has significantly accelerated the DD_SC for business people because it demands people to keep social distance as a preventive measure against the Covid19 effect (Song et al, 2021;Zhang et al, 2021). So, the most accessible means of servicing customers was by familiarizing themselves with digital capabilities that assist online businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Covid19 has significantly accelerated the DD_SC for business people because it demands people to keep social distance as a preventive measure against the Covid19 effect (Song et al. , 2021; Zhang et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, risk-related constraints were measured using 13 items [ 31 , 35 , 40 , 59 ]. To capture the participants’ motives for outdoor leisure or travel, items (e.g., relaxation, enjoying beautiful natural scenery) were developed based on the review by Zhang [ 60 ] on travel motivation. Subsequently, adaptive response was measured using statements such as seeking information and actions to prevent viral infection, whereas maladaptive perception was measured using six items.…”
Section: Methodsmentioning
confidence: 99%